2015
DOI: 10.1051/0004-6361/201425266
|View full text |Cite
|
Sign up to set email alerts
|

TOPoS

Abstract: Context. In the course of the Turn Off Primordial Stars (TOPoS) survey, aimed at discovering the lowest metallicity stars, we have found several carbon-enhanced metal-poor (CEMP) stars. These stars are very common among the stars of extremely low metallicity and provide important clues to the star formation processes. We here present our analysis of six CEMP stars. Aims. We want to provide the most complete chemical inventory for these six stars in order to constrain the nucleosynthesis processes responsible f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
232
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(261 citation statements)
references
References 173 publications
25
232
1
Order By: Relevance
“…Several studies have confirmed the existence of the carbon bands, and have populated them with more stars (e.g., Bonifacio et al 2015;Hansen et al 2015). Here we discuss the behaviour of the heavy elements and how they associate with these bands in order to better constrain the astrophysical sites and processes that enriched the different subclasses of CEMP stars.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Several studies have confirmed the existence of the carbon bands, and have populated them with more stars (e.g., Bonifacio et al 2015;Hansen et al 2015). Here we discuss the behaviour of the heavy elements and how they associate with these bands in order to better constrain the astrophysical sites and processes that enriched the different subclasses of CEMP stars.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, the normal binary frequency of the CEMP-no stars (Starkenburg et al 2014;Bonifacio et al 2015;Hansen et al 2016a) suggests that their abundances reflect the composition of the gas from which they were born.…”
Section: Sr and Bamentioning
confidence: 95%
See 2 more Smart Citations
“…Spite et al (2013) found that when the absolute carbon abundances, A(C), of CEMP stars are presented as a function of [Fe/H], two distinct bands are found; the high and low carbon bands. This work was subsequently extended in Bonifacio et al (2015). The high carbon band contains the most iron-rich CEMP stars, and is populated by all four subclasses of CEMP star.…”
Section: Introductionmentioning
confidence: 98%